Consideraciones para el diseno de un programa de mejoramiento de yuca - Hershey, Clair H. (International Center for Tropical Agriculture, 1991)
Several important areas in which plant breeders must make decisions are outlined; the factors affecting decision-making in given situations are also analyzed. Three aspects that markedly influence the general structure of a cassava breeding program are discussed in detail, namely (1) definition of objetives; (2) identification and characterization of target area; and (3) chacteristics of the genetic variability under manipulation. Regarding the 2nd point, plant breeders must make decisions regarding 3 major aspects: (1) characterization of the environment (socioeconomic, agroclimatic, biological); (2) environmental subdivision; and (3) selection of trial sites. A broad, tentative classification of cassava environments, based on environmental factors affecting crop adaptation and productivity, is presented. When designing the program, other aspects that should be taken into account are the sources of germplasm (local, national, and international collections; improved germplasm) and the forms of germplasm (vegetative or botanical seed); the implications of these aspects in program designing are discussed. The need for a broad, comprehensive view to design a successful program is highlighted. (CIAT)